Head and neck cancer and occupational exposure to leather dust: results from the ICARE study, a French case-control study - Loredana Radoï; Fatoumata Sylla; Mireille Matrat; Christine Barul; Gwenn Menvielle; Patricia Delafosse; Isabelle Stücker; Danièle Luce; ICARE study group (BMC, 2019)
Abstract Background Leather dust is an established carcinogen of the sinonasal cavities; however, evidence is lacking regarding its association with other head and neck cancers (HNC). To date, few studies have been conducted on the association between occupational leather dust exposure and the risk of oral, pharyngeal, and laryngeal cancers. The objective of this study was to investigate the association between the risk of HNC and occupational exposure to leather dust. Methods Lifestyle habits and occupational history were collected for 2161 patients with squamous cell carcinoma of oral cavity, pharynx, and larynx, and 3555 controls, using a standardized questionnaire. Occupational exposure to leather dust was assessed using a job-exposure matrix. Odds ratios (OR) and 95% confidence intervals (CI) for HNC globally and by subsite were estimated using multivariate unconditional, and polytomous logistic regressions, respectively. Results Cumulative lifetime exposure to leather dust < 6 mg/m3-years was associated with an increased risk of laryngeal cancer (OR = 2.26, 95% CI: 1.07-4.76); higher levels were not related to elevated risks of HNC. Some tasks performed and the use of some glues were associated with elevated, although non-significant, risks of HNC. No dose-response relationships were observed. Conclusion Our study did not provide enough evidence for an increased risk of HNC related to occupational exposure to leather dust. Further studies are needed to understand the risks of specific tasks in the leather industry.